Exploring the role of smartphone use and demographic factors in predicting nomophobia among university students in Jordan - Nahla Al Ali; Sara Matarneh (International Journal of Adolescence and Youth)
Nomophobia is one of the problems of the overuse of mobile phones and the fear of missing out, which has become prevalent among university students and interferes with their daily activities. This study aimed to investigate the extent and potential predictors of nomophobia among university students, including the role of smartphone use and demographic factors. The study surveyed 636 students from various academic levels using the Nomophobia Questionnaire (NMP-Q) through an online cross-sectional survey. The results showed that nomophobia varied in severity from mild to severe. Females experienced nomophobia more frequently than males (p < .001). Gender, phone-checking frequency, number of calls made and received per day, and number of texts received per day were all predictors of nomophobia. With such knowledge, targeted interventions and support systems can be developed to cater to these students’ unique requirements and struggles regarding smartphone use and nomophobia.